IDENTIFICATION OF WRITEN WORDS IN DEAF CHILDREN: THE ROLE OF PHONOLOGY - Martínez de Antoñana Ugarte, Rosa; Augusto Landa, José María (Anales de Psicología / Annals of Psychology, 2002)
Theoretical models of reading process affirm that a skilled reader have to make use of two different sources of information from written material. The aim of this study was to see what extent dual models of reading could be applied to performance of Spanish deaf orally educated readers. 55 deaf children (from 2nd. to 6th grade) were asked to read aloud a selection of words and a set of matched nonwords. The written stimuli varied in their frequencyand length. The pattern of results suggests that many deaf scholars take use of the phonological knowledge about written stimuli, but in a limited mode, and that the visual process (the orthographic information) is no used, or it do it in a very restricted way.